Brazil-Africa Relations. Historical Dimensions and Contemporary Engagements from the 1960 to the Present - Seibert, Gerhard; Visentini, Paulo Fagundes (2019)
When Lula da Silva became President of Brasil in 2003 he declared Africa a priority of his country's ambitious global policy. During his presidency, Brazil became one of the key emergent powers in Africa through strengthening political ties, development cooperation and trade with the continent. While the Dilma and Temer presidencies had other political priorities, strong links with the continent continued to exist. Tracing Brazil-Africa relations from the early 16th century and the slave trade, through their decline during European colonialism, resurgence following many African countries' independence, the ups and downs during Brazil's military rule in the 1060s and '70s, to the expansion of its interests under Lula and during the Dilma and Temer years, the authors show their long history. Taking a broad range of perspectives, they examine: the way in which the rights of those of African descent in Brazil have become increasingly recognized without having brought racial equality; the strengthening of multilateral links with the continent and the growth of South-South cooperation; and Brazil-Africa relations in the South Atlantic context. The final chapter looks at the wider implications of the present political and economic crises for Brazil's future foreign policy in Africa, and the likely impact of new president Jair Bolsonaro elected in late 2018.